Utilization of Interactive Flat Panel (IFP) Technology in Islamic Religious Education Learning to Build Learning Motivation of Class VIII Students of Muhammadiyah Middle School Bima City - Ade Nurfadillah; Syafruddin; Irwan (Lembaga Bale Literasi, 2026)
This study aims to investigate in depth the use of Interactive Flat Panel (IFP) technology in Islamic Religious Education (PAI) learning to build learning motivation in class VIII students of Muhammadiyah Middle School Bima City. This research uses a qualitative descriptive approach with a field research type, which aims to describe and understand phenomena regularly based on real conditions in the field without testing certain hypotheses. Data was collected through observation, interviews and documentation, including document analysis and field notes, then presented in the form of narrative description. The results of the study show that the use of Interactive flat panel (IFP) technology, in Islamic Religious Education learning, it is able to build students' learning motivation, which is characterized by increased attention, activity, and student interest during the learning process. Teachers utilize various interactive features such as visual displays, videos, and other digital media so that learning becomes more interesting and not monotonous. In addition, the use of IFP helps students understand the material more concretely and contextually. However, there are several obstacles such as limited teacher ability in operating technology and suboptimal supporting facilities. Thus, the use of IFP technology can be an innovative alternative in increasing students' learning motivation in Islamic Religious Education learning